Favorable Nonclinical Safety Profile of RSVpreF Bivalent Vaccine in Rats and Rabbits - Jun Zhou; Christopher J. Bowman; Vicki R. Markiewicz; Balasubramanian Manickam; Emily Gomme; Rani S. Sellers; Cynthia M. Rohde (Vaccines)
Background: Respiratory syncytial virus (RSV) infections usually cause mild, cold-like symptoms in most people, but are a leading infectious disease causing infant death and hospitalization and can result in increased morbidity and mortality in older adults and at-risk individuals. Pfizer has developed Abrysvo®, an unadjuvanted bivalent recombinant protein subunit vaccine containing prefusion-stabilized fusion (F) proteins representing RSV A and RSV B subgroups (RSVpreF). It is the only RSV vaccine approved for both maternal immunization to protect infants and active immunization of older adults (≥60 years) and 18–59-year-old individuals with high-risk conditions for prevention of RSV disease. Methods: Nonclinical safety studies, including a repeat-dose toxicity (RDT) study in rats and a combined developmental and reproductive toxicity (DART) study in rabbits, were conducted to support early clinical development. Study designs and parameters evaluated in these studies were consistent with principles and practices as outlined in relevant regulatory guidelines. RSVpreF bivalent vaccine, with or without Al(OH)3, was administered intramuscularly (IM) at 2× the human dose to animals in both studies. Results: Locally tolerated, reversible, inflammatory responses at the injection sites and the draining lymph nodes were observed as typical findings following vaccination. No effect of RSVpreF, with or without Al(OH)3, was observed on female fertility or on embryo–fetal or postnatal survival, growth, or development in the DART study. In both studies, robust immune responses to both RSV A and B antigens were observed, especially with the Al(OH)3 formulation. Conclusions: RSVpreF was well-tolerated both locally and systemically without any adverse effects on reproductive and developmental endpoints.